2017
DOI: 10.1371/journal.pone.0182917
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Potentilla fruticosa L. leaves by iTRAQ reveals responses to heat stress

Abstract: High temperature is an important environmental factor that affects plant growth and crop yield. Potentilla fruticosa L. has a developed root system and characteristics of resistance to several stresses (e.g., high temperature, cold, drought) that are shared by native shrubs in the north and west of China. To investigate thermotolerance mechanisms in P. fruticosa, 3-year-old plants were subjected to a high temperature of 42°C for 1, 2, and 3 days respectively before analysis. Then, we studied changes in cell ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Abiotic stresses (such as low-temperature, drought, and salt) will lead to the degradation of photosynthesis-related proteins in plants, further reducing plant light energy utilization and being more susceptible to light inhibition [35][36][37]. In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the xation of CO2 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic stresses (such as low-temperature, drought, and salt) will lead to the degradation of photosynthesis-related proteins in plants, further reducing plant light energy utilization and being more susceptible to light inhibition [35][36][37]. In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the xation of CO2 [38].…”
Section: Discussionmentioning
confidence: 99%
“…The study of [ 3 ] found that the alteration of proteins associated with antioxidant defense, photosynthesis, and HSPs played positive roles in enhancing heat adaptation in grape ( Vitis vinifera ). Heat stress damaged cell membranes and photosynthesis along with significant regulation of proteins involved in abiotic stress defense, photosynthesis, and signal transduction in leaves of Potentilla Fruticosa [ 4 ]. Differential abundance of proteins participating in stress defense, energy, and nucleotide metabolism, and signal transduction was related to the adaptation to heat stress in mustard ( Brassica juncea ) plants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic stresses (such as low temperature, drought, and salt) will lead to the degradation of photosynthesis-related proteins in plants, further reducing plant light energy utilization and being more susceptible to light inhibition [35][36][37]. In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the fixation of CO2 [38].…”
Section: Response Mechanism Of Lysine Crotonylation and Chrysanthemummentioning
confidence: 99%